Common variants within MECP2 confer risk of systemic lupus erythematosus. - Amr H Sawalha; Ryan Webb; Shizhong Han; Jennifer A Kelly; Kenneth M Kaufman; Robert P Kimberly; Marta E Alarcón-Riquelme; Judith A James; Timothy J Vyse; Gary S Gilkeson; Chan-Bum Choi; R Hal Scofield; et al. (PLoS ONE, 2008)
Systemic lupus erythematosus (SLE) is a predominantly female autoimmune disease that affects multiple organ systems. Herein, we report on an X-chromosome gene association with SLE. Methyl-CpG-binding protein 2 (MECP2) is located on chromosome Xq28 and encodes for a protein that plays a critical role in epigenetic transcriptional regulation of methylation-sensitive genes. Utilizing a candidate gene association approach, we genotyped 21 SNPs within and around MECP2 in SLE patients and controls. We identify and replicate association between SLE and the genomic element containing MECP2 in two independent SLE cohorts from two ethnically divergent populations. These findings are potentially related to the overexpression of methylation-sensitive genes in SLE.